Independent Learning Program Policies in the Preparation of the Thematic Learning Implementation Plan (RPP) - Syakila, Syarifah Nur Wahyu; Setyowati, Wiwid; Lestari, Dwi Endah (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2021)
With the development of the era in the era of the industrial revolution 4.0, the world of education continues to develop and improve 21st century competencies. Based on the program initiated by the Minister of Education and Culture of the Republic of Indonesia, the Ministry of Education and Culture has set 4 main policies in the field of national education through the